Testosterone and 17β-Estradiol Induce Glandular Prostatic Growth, Bladder Outlet Obstruction, and Voiding Dysfunction in Male Mice - Nicholson, Tristan M. (Endocrine Society, 2012)
Benign prostatic hyperplasia (BPH) and bladder outlet obstruction (BOO) are common in older men and can contribute to lower urinary tract symptoms that significantly impact quality of life. Few existing models of BOO and BPH use physiological levels of hormones associated with disease progression in humans in a genetically manipulable organism. We present a model of BPH and BOO induced in mice with testosterone (T) and 17β-estradiol (E(2)). Male mice were surgically implanted with slow-releasing sc pellets containing 25 mg T and 2.5 mg E(2) (T+E(2)). After 2 and 4 months of hormone treatment, we evaluated voiding patterns and examined the gross morphology and histology of the bladder, urethra, and prostate. Mice treated with T+E(2) developed significantly larger bladders than untreated mice, consistent with BOO. Some mice treated with T+E(2) had complications in the form of bladder hypertrophy, diverticula, calculi, and eventual decompensation with hydronephrosis. Hormone treatment caused a significant decrease in the size of the urethral lumen, increased prostate mass, and increased number of prostatic ducts associated with the prostatic urethra, compared with untreated mice. Voiding dysfunction was observed in mice treated with T+E(2), who exhibited droplet voiding pattern with significantly decreased void mass, shorter void duration, and fewer sustained voids. The constellation of lower urinary tract abnormalities, including BOO, enlarged prostates, and voiding dysfunction seen in male mice treated with T+E(2) is consistent with BPH in men. This model is suitable for better understanding molecular mechanisms and for developing novel strategies to address BPH and BOO.